(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The paper proposed a base-conceptual view of the conflict of art and technolo-gy presents an original analysis of the conflict-epic prose works such as the novel. This technology has been tested on the material of one of the most difficult in terms of con-flict of novel of V. Vinnychenko «Gods», made conclusions about its effectiveness.